2005
DOI: 10.1002/app.21496
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous polyamide 66/syndiotactic polystyrene blends: Phase structure and thermal and mechanical properties

Abstract: ABSTRACT:The structural and physical properties of polyamide 66 (PA66)/syndiotactic polystyrene (sPS) blends were studied with electron microscopy, wide-angle X-ray scattering (WAXS), differential scanning calorimetry (DSC), dynamic mechanical thermal analysis, and tensile creep, stress-strain, and impact measurements. Attention was primarily concentrated on blends with sPS weight fractions (w 2 ) in the range of 0 Ͻ w 2 Յ 0.50. DSC and WAXS showed that the integral crystallinity of the PA66 and sPS components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…If the interfacial adhesion is weak, the fracture propagates along the interphase and, as a result, both phases are clearly distinguishable on the fracture surfaces . If the interfacial adhesion is strong, the fracture propagates straight through the strongly adhering phases and, consequently, the two phases are hard to differentiate , which was observed in the HDPE/COC blends (Fig. ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…If the interfacial adhesion is weak, the fracture propagates along the interphase and, as a result, both phases are clearly distinguishable on the fracture surfaces . If the interfacial adhesion is strong, the fracture propagates straight through the strongly adhering phases and, consequently, the two phases are hard to differentiate , which was observed in the HDPE/COC blends (Fig. ).…”
Section: Resultsmentioning
confidence: 87%
“…and ). Although the fracture was performed at liquid nitrogen temperature, that is, far below the T g of blend components, the fracture surface was not completely brittle (no sharp fracture lines ) and HDPE phase exhibited typical microplastic deformations, which develop due to local overheating during the fracture .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dynamic mechanical measurements over a range of temperatures provide valuable insight into the structure, morphology and properties of polymeric blends and composites. A lot of dynamic mechanical analyses on polymeric blends and composites have been done [1][2][3][4]. Zhang et al [1] measured dynamic mechanical properties of composites filled with SMA particles and short fibers, and found that the storage modulus reaches the maximum at the SMA phase transformation temperature of approximate 120˚C.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a higher storage modulus enhancement was obtained when the organo-clay nanoplatelets were delaminated and more homogeneously dispersed. Kolarik [4] researched the Phase structure and thermal and mechanical properties of heterogeneous polyamide 66/syndiotactic polystyrene blends, and found that storage modulus (125˚C) noticeably declined with weight fraction and thus showed that sPS did not improve the dimensional stability of the blends at elevated temperatures. Since 1998, Liang et al [5][6][7][8][9] have investigated the effects of glass bead content and size on the viscoelastic properties of filled polyolefin composites, and get some useful findings.…”
Section: Introductionmentioning
confidence: 99%